Täter- und Opfergeschichten. Schuld in Alois Hotschnigs Prosawerken «Aus», «Leonardos Hände» und «Ludwigs Zimmer» (Studia austriaca, 2014)
The assumption this article is based on is that guilt is perhaps the most important theme in Alois Hotschnig’s writing. This article therefore aims at analyzing Hotschnig’s focus on the theme of guilt in his novels. Three examples of Hotschnig’s prose work serve as case studies: his debut Aus, and the two novels Leonardos Hände, and Ludwigs Zimmer. Since guilt seems to be a very important topic in the Austrian literary tradition, this article also tries to establish whether and how Hotschnig takes up this grand Austrian tradition of writing about guilt.